Magnetic composite material and preparation method and application thereof

By reasonably matching FeSiNbBCu nanocrystals and FeNi alloy powders with different particle sizes in magnetic composite materials, fully filling the particle pores, solving the problem of low density of magnetic composite materials, improving magnetic permeability and reducing high-frequency losses.

CN119517534APending Publication Date: 2025-02-25HENGDIAN GRP DMEGC MAGNETICS CO LTD +1

Patent Information

Application Number
CN202411689705.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The density of existing magnetic composite materials is low, affecting their magnetic permeability and high-frequency performance.

Method used

By selecting FeSiNbBCu nanocrystals and FeNi alloy powders of different particle sizes and reasonably matching the particle size between the two, the FeNi alloy powder with small particle sizes is fully filled into the particle pores of FeSiNbBCu nanocrystals, reducing porosity, improving density and magnetic properties.

Benefits of technology

It achieves the improvement of the density and permeability of magnetic composite materials, while reducing high-frequency losses, simple process and easy to produce on a large scale.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a magnetic composite material and a preparation method and application thereof, the preparation method comprises the following steps: mixing nanocrystalline, FeNi alloy powder and a binder, and then baking to obtain the magnetic composite material, the average particle size of the nanocrystal is 10 [mu] m-50 [mu] m; the average particle size of the FeNi alloy powder ranges from 0.1 micrometer to 10 micrometers. The FeSiNbBCu nanocrystals and the FeNi alloy powder with different particle sizes are selected, and the particle sizes of the FeSiNbBCu nanocrystals and the FeNi alloy powder are reasonably matched, so that particle pores of the FeSiNbBCu nanocrystals can be fully filled with the FeNi alloy powder with small particle sizes, the porosity of the magnetic composite material can be reduced, the density of the magnetic composite material can be improved, and the magnetic performance of the magnetic composite material can also be improved. The method provided by the invention is simple in process and convenient for large-scale production, and the prepared magnetic composite material is high in magnetic conductivity and low in high-frequency loss.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnetic materials, and in particular to a magnetic material and a preparation method and application thereof, and in particular to a magnetic composite material and a preparation method and application thereof. Background Art

[0002] At present, with the rapid development of the electronics and electrical industry, magnetic materials are increasingly used in high-frequency switching power supplies and high-precision transformers. With the diversity of customer needs, the performance requirements for magnetic materials are becoming more and more refined. Therefore, developing a magnetic material with high frequency, low loss and high magnetic permeability is a key issue to be solved in the field of magnetic material technology.

[0003] Iron-based nanocrystalline materials have become key materials in high-frequency switching power supplies and high-precision transformers due to their high-frequency, low-loss, and high-magnetic induction properties. They can be widely used in wireless charging equipment, transformers, high-frequency inverter technology, and high-precision transformers. However, the porosity of the magnetic material prepared using only iron-based nanocrystalline materials as raw materials is relatively high, which in turn affects the magnetic permeability of the magnetic material.

[0004] FeNi alloy material has excellent magnetic properties and excellent corrosion resistance. When combined with iron-based nanocrystalline materials, it can improve the density of iron-based nanocrystalline materials, and further improve the magnetic permeability of magnetic materials. CN107240471A discloses a composite magnetic powder with high saturation magnetic induction intensity, a magnetic core and a preparation method thereof. The composite magnetic powder is obtained by mixing two powders, and then certain additives are added. After pressing and annealing, the magnetic core of the present invention can be obtained. However, in the invention, the particle sizes of the two magnetic powders are the same, and the density of the prepared magnetic core is low.

[0005] Therefore, how to improve the density of magnetic composite materials and thus improve their magnetic permeability has become a problem that needs to be solved urgently. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a magnetic composite material and its preparation method and application. The present invention selects FeSiNbBCu nanocrystals and FeNi alloy powders of different particle sizes and reasonably matches the particle sizes between the two, so that the FeNi alloy powder with a small particle size can be fully filled into the particle pores of the FeSiNbBCu nanocrystals, thereby reducing the porosity of the magnetic composite material, improving its density, and also improving its magnetic properties. The method provided by the present invention has a simple process and is convenient for large-scale production. The prepared magnetic composite material can also reduce high-frequency loss while maintaining high magnetic permeability.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In the first aspect, the present invention provides a method for preparing a magnetic composite material, the preparation method comprising the following steps: mixing FeSiNbBCu nanocrystals, FeNi alloy powder and a binder, and then baking to obtain the magnetic composite material; the average particle size of the FeSiNbBCu nanocrystals is 10μm-50μm; the average particle size of the FeNi alloy powder is 0.1μm-10μm.

[0009] The present invention selects FeSiNbBCu nanocrystals and FeNi alloy powders of different particle sizes and reasonably matches the particle sizes between the two, so that the FeNi alloy powder with a small particle size can be fully filled into the particle pores of the FeSiNbBCu nanocrystals, thereby reducing the porosity of the magnetic composite material, improving its density, and also improving its magnetic properties. The method provided by the present invention has a simple process and is convenient for large-scale production, and the prepared magnetic composite material can also reduce high-frequency loss while maintaining high magnetic permeability.

[0010] Specifically, the average particle size of the FeSiNbBCu nanocrystals can be 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm or 50μm, and the average particle size of the FeNi alloy powder can be 0.1μm, 0.5μm, 1μm, 3μm, 5μm, 8μm or 10μm, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0011] Preferably, the chemical formula of the FeSiNbBCu nanocrystal is Fe a Si b Nb c B d Cu e , 5≤b≤20, 5≤c≤20, 0.5≤d≤15, 0.5≤e≤15, and satisfy a+b+c+d+e=100; wherein b can be 5, 8, 10, 15 or 20, c can be 5, 8, 10, 15 or 20, d can be 0.5, 3, 8, 10, 12 or 15, e can be 0.5, 3, 8, 10, 12 or 15, but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0012] Preferably, in the FeNi alloy powder, the mass ratio of iron to nickel is 1:(0.8-1.2), for example, it can be 1:0.8, 1:0.9, 1:1, 1:1.1 or 1:1.2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0013] Preferably, the binder comprises a combination of a first binder, a second binder, a third binder and a fourth binder, the first binder comprises polyvinyl butyral, the second binder comprises Al 2 [(OH) 4 / Si 2 O 5 ], the third adhesive includes epoxy resin, and the fourth adhesive includes dodecyltrimethylsilane.

[0014] The binder of the present invention comprises polyvinyl butyral ester, Al 2 [(OH) 4 / Si 2 O 5 ], epoxy resin and dodecyltrimethylsilane, by coupling the binder epoxy resin and the coupling agent dodecyltrimethylsilane, and adding polyvinyl butyral ester and Al 2 [(OH) 4 / Si 2 O 5 ], strengthen the coordination of the binder and the coupling agent. The invention adopts a specific binder, which can not only improve the bonding effect of the binder, improve the density of the magnet, and reduce high-frequency loss, but also simplify the process steps and reduce the production cost.

[0015] Preferably, the preparation method of the binder comprises the following steps: 2 [(OH) 4 / Si 2 O 5 ], epoxy resin and dodecyltrimethylsilane are dissolved in an organic solvent in proportion, and stirred until the organic solvent is completely volatilized to obtain a mixture; the mixture is sieved to obtain the adhesive.

[0016] Preferably, the organic solvent comprises ethanol and / or acetone.

[0017] Preferably, the mesh size of the sieving screen is 60-100 mesh, for example, 60 mesh, 70 mesh, 80 mesh, 90 mesh or 100 mesh, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] Preferably, the mass ratio of the first binder, the second binder, the third binder and the fourth binder is (1-2):(1-2):(2-3):(1-2), for example, it can be 1:1:2:1, 1:1:3:1, 1:1:2:2, 1:2:2:1, 2:2:2:1 or 2:2:3:2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] Preferably, the mass ratio of the FeSiNbBCu nanocrystals to the FeNi alloy powder is 1:(0.5-2), for example, it can be 1:0.5, 1:1, 1:1.5, 1:1.8 or 1:2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] The present invention further improves the density of the magnetic composite material by adjusting the mass ratio of FeSiNbBCu nanocrystals and FeNi alloy powder and the proportion of small-size FeNi alloy powder filled into the pores of large-size FeSiNbBCu nanocrystal particles, and can optimize the structure and size. The dense structure makes the grains evenly distributed, reduces gaps and defects, and thus improves the magnetic permeability and reduces hysteresis loss.

[0021] Preferably, the sum of the mass addition amounts of the FeSiNbBCu nanocrystals and the FeNi alloy powder is M1, the mass addition amount of the binder is M2, and M2 is 1%-2% of M1, for example, it can be 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, before the mixing, the FeSiNbBCu nanocrystals are further annealed.

[0023] Preferably, the holding temperature of the annealing treatment is 550°C-650°C, for example, it can be 550°C, 570°C, 590°C, 600°C, 620°C or 650°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] Preferably, the holding time of the annealing treatment is 1h-5h, for example, it can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] The present invention can effectively improve the magnetic permeability of the magnetic composite material by performing a preliminary annealing treatment on the FeSiNbBCu nanocrystalline material, and can also reduce its high-frequency loss. Furthermore, the present invention can further improve the diffusion and migration speed of atoms, increase the growth speed of grains, and increase the activity and stability of the nanocrystalline material by controlling the insulation temperature of the annealing treatment; on the other hand, it can prevent the grain size from growing too fast, further improve the crystallinity of the nanocrystalline, and thus improve the density and uniformity of the magnetic composite material.

[0026] Preferably, the heating rate of the annealing treatment is 1°C / min-3°C / min, for example, it can be 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min or 3°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] Preferably, the ambient atmosphere of the annealing treatment is a first inert gas atmosphere.

[0028] Preferably, the first inert gas atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.

[0029] Preferably, the mixing method comprises ball milling.

[0030] Preferably, the ball milling comprises dry ball milling.

[0031] Preferably, compression molding is performed after mixing and before baking.

[0032] Preferably, the pressing pressure is 300 MPa-3000 MPa, for example, 300 MPa, 800 MPa, 1000 MPa, 1500 MPa, 2000 MPa, 2500 MPa or 3000 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] Preferably, the baking insulation temperature is 150°C-300°C, for example, it can be 150°C, 170°C, 200°C, 250°C, 290°C or 300°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] Preferably, the baking holding time is 1h-5h, for example, it can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h or 5h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] The present invention can improve the magnetic properties of the magnetic composite material by baking. Furthermore, the present invention can ensure the thermal stability of the adhesive by controlling the heat preservation temperature of baking, further improve the bonding strength and bonding effect, and can also reduce the residual stress inside the magnetic composite material, further improving the magnetic properties of the magnetic composite material.

[0036] Preferably, the baking heating rate is 3°C / min-5°C / min, for example, it can be 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min or 5°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the baking environment atmosphere is a second inert gas atmosphere.

[0038] Preferably, the second inert gas atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.

[0039] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0040] (1) annealing the FeSiNbBCu nanocrystals in a first inert gas atmosphere to obtain pretreated FeSiNbBCu nanocrystals, wherein the annealing treatment is performed at a holding temperature of 550°C-650°C, the annealing treatment time is 1h-5h, and the annealing treatment heating rate is 1°C / min-3°C / min.

[0041] (2) Pretreated FeSiNbBCu nanocrystals and FeNi alloy powder are mixed in proportion to obtain mixed magnetic powder, wherein the average particle size of the pretreated FeSiNbBCu nanocrystals is 10 μm-50 μm, and the average particle size of the FeNi alloy powder is 0.1 μm-10 μm.

[0042] (3) After adding the binder to the mixed magnetic powder in proportion, the mixed magnetic powder is molded, pressed and baked in sequence to obtain the magnetic composite material, the molding and pressing pressure is 300MPa-3000MPa, the baking insulation temperature is 150℃-300℃, the baking insulation time is 1h-5h, the baking heating rate is 3℃ / min-5℃ / min, and the baking environment atmosphere is the second inert gas atmosphere.

[0043] In a second aspect, the present invention provides a magnetic composite material, which is prepared by the preparation method described in the first aspect.

[0044] Preferably, the magnetic permeability of the magnetic composite material under 100kHz / 1V conditions is ≥40H / m, for example, it can be 40H / m, 42H / m, 44H / m, 46H / m, 48H / m or 50H / m, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] Preferably, the loss of the magnetic composite material under the condition of 1MHz / 50mT is ≤2000mW / cm 3 , for example, it can be 1700mW / cm 3 、1750mW / cm 3 、1800mW / cm 3 、1900mW / cm 3 、1950mW / cm 3 or 2000mW / cm 3, but not limited to the listed values, other unlisted values ​​within the numerical range are also applicable.

[0046] In a third aspect, the present invention provides an application of the magnetic composite material as described in the second aspect, wherein the magnetic composite material is applied to aerospace, communication or new energy.

[0047] Compared with the prior art, the present invention has at least the following beneficial effects:

[0048] (1) The present invention selects FeSiNbBCu nanocrystals and FeNi alloy powders of different particle sizes and reasonably matches the particle sizes between the two, so that the FeNi alloy powder with a small particle size can be fully filled into the particle pores of the FeSiNbBCu nanocrystals, thereby reducing the porosity of the magnetic composite material, increasing its density, and also improving its magnetic properties.

[0049] (2) The method provided by the present invention has a simple process and is convenient for large-scale production. In addition, the prepared magnetic composite material can reduce high-frequency loss while maintaining high magnetic permeability. DETAILED DESCRIPTION

[0050] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0051] The polyvinyl butyral used in the following examples is produced by Shanghai MacLean Biochemical Technology Co., Ltd., with a CAS number of 63148-65-2 and a product number of P815775-100g.

[0052] Example 1

[0053] This embodiment provides a method for preparing a magnetic composite material, the preparation method comprising the following steps:

[0054] (1) Fe 82 Si 9 Nb 6 B 2 Cu 1 The nanocrystals were annealed in a nitrogen atmosphere to obtain the pre-treated Fe 82 Si 9 Nb 6 B 2 Cu 1 The nanocrystal has a holding temperature of 600°C, a holding time of 2h, and a heating rate of 2°C / min.

[0055] (2) Mix the pretreated Fe in proportion 82 Si9 Nb 6 B 2 Cu 1 Nanocrystalline and FeNi alloy powder to obtain mixed magnetic powder, wherein the mass ratio of iron to nickel in the FeNi alloy powder is 1:1; the pretreated Fe 82 Si 9 Nb 6 B 2 Cu 1 The average particle size of the nanocrystals is 20 μm, the average particle size of the FeNi alloy powder is 1 μm, and the pretreated Fe 82 Si 9 Nb 6 B 2 Cu 1 The mass ratio of nanocrystals to FeNi alloy powder is 1:1.

[0056] (3) After adding a binder to the mixed magnetic powder in proportion, the mixed magnetic powder is molded, pressed and baked in sequence to obtain the magnetic composite material, wherein the binder is polyvinyl butyral ester, Al 2 [(OH) 4 / Si 2 O 5 ], epoxy resin and dodecyl trimethyl silane, the polyvinyl butyral ester, Al 2 [(OH) 4 / Si 2 O 5 ], epoxy resin and dodecyltrimethylsilane in a mass ratio of 1:1:3:2, the pretreated Fe 82 Si 9 Nb 6 B 2 Cu 1 The sum of the mass addition amounts of nanocrystalline and FeNi alloy powder is M1, the mass addition amount of the binder is M2, M2 is 1.5% of M1, the molding and pressing pressure is 1000MPa, the baking insulation temperature is 220°C, the baking insulation time is 4h, the baking heating rate is 4°C / min, and the baking environment atmosphere is a nitrogen gas atmosphere.

[0057] Example 2

[0058] This embodiment provides a method for preparing a magnetic composite material, the preparation method comprising the following steps:

[0059] (1) Fe 81.5 Si 8.5 Nb 6 B 2.5 Cu 1.5The nanocrystals were annealed in an argon atmosphere to obtain the pre-treated Fe 81.5 Si 8.5 Nb 6 B 2.5 Cu 1.5 Nanocrystal, the holding temperature of the annealing treatment is 550°C, the holding time of the annealing treatment is 5h, and the heating rate of the annealing treatment is 1°C / min.

[0060] (2) Mix the pretreated Fe in proportion 81.5 Si 8.5 Nb 6 B 2.5 Cu 1.5 Nanocrystalline and FeNi alloy powder to obtain mixed magnetic powder, wherein the mass ratio of iron to nickel in the FeNi alloy powder is 1:0.8, and the Fe 81.5 Si 8.5 Nb 6 B 2.5 Cu 1.5 The average particle size of the nanocrystals is 50 μm, the average particle size of the FeNi alloy powder is 10 μm, and the pretreated Fe 81.5 Si 8.5 Nb 6 B 2.5 Cu 1.5 The mass ratio of nanocrystals to FeNi alloy powder is 1:0.5.

[0061] (3) After adding a binder to the mixed magnetic powder in proportion, the mixed magnetic powder is molded, pressed and baked in sequence to obtain the magnetic composite material, wherein the binder is polyvinyl butyral ester, Al 2 [(OH) 4 / Si 2 O 5 ], epoxy resin and dodecyl trimethyl silane, the polyvinyl butyral ester, Al 2 [(OH) 4 / Si 2 O 5 ], epoxy resin and dodecyltrimethylsilane in a mass ratio of 1:1:2:1, the pretreated Fe 81.5 Si 8.5 Nb 6 B 2.5 Cu 1.5The sum of the mass addition of nanocrystalline and FeNi alloy powder is M1, the mass addition of the binder is M2, M2 is 1% of M1, the molding and pressing pressure is 3000MPa, the baking insulation temperature is 150°C, the baking insulation time is 5h, the baking heating rate is 3°C / min, and the baking environment atmosphere is argon gas atmosphere.

[0062] Example 3

[0063] This embodiment provides a method for preparing a magnetic composite material, the preparation method comprising the following steps:

[0064] (1) Fe 81.5 Si 9 Nb 6.5 B 2 Cu 1 The nanocrystals were annealed in a nitrogen atmosphere to obtain the pre-treated Fe 81.5 Si 9 Nb 6.5 B 2 Cu 1 The nanocrystal has a holding temperature of 650°C, a holding time of 1h, and a heating rate of 3°C / min.

[0065] (2) Mix the pretreated Fe in proportion 81.5 Si 9 Nb 6.5 B 2 Cu 1 Nanocrystalline and FeNi alloy powder to obtain mixed magnetic powder, wherein the mass ratio of iron to nickel in the FeNi alloy powder is 1:1.2, and the pretreated Fe 81.5 Si 9 Nb 6.5 B 2 Cu 1 The average particle size of the nanocrystals is 10 μm, the average particle size of the FeNi alloy powder is 0.1 μm, and the pretreated Fe 81.5 Si 9 Nb 6.5 B 2 Cu 1 The mass ratio of nanocrystals to FeNi alloy powder is 1:2.

[0066] (3) After adding a binder to the mixed magnetic powder in proportion, the mixed magnetic powder is molded, pressed and baked in sequence to obtain the magnetic composite material, wherein the binder is polyvinyl butyral ester, Al 2 [(OH) 4 / Si 2 O5 ], epoxy resin and dodecyl trimethyl silane, the polyvinyl butyral ester, Al 2 [(OH) 4 / Si 2 O 5 ], epoxy resin and dodecyltrimethylsilane in a mass ratio of 2:2:3:2, the pretreated Fe 81.5 Si 9 Nb 6.5 B 2 Cu 1 The sum of the mass addition amounts of nanocrystalline and FeNi alloy powder is M1, the mass addition amount of the binder is M2, M2 is 2% of M1, the molding and pressing pressure is 300MPa, the baking insulation temperature is 300°C, the baking insulation time is 1h, the baking heating rate is 5°C / min, and the baking environment atmosphere is a nitrogen gas atmosphere.

[0067] Example 4

[0068] The only difference between this embodiment and embodiment 1 is that, except that the holding temperature of the annealing treatment in step (1) is 500° C., the rest is the same as embodiment 1.

[0069] Example 5

[0070] The only difference between this embodiment and embodiment 1 is that, except that the holding temperature of the annealing treatment in step (1) is 700° C., the rest is the same as embodiment 1.

[0071] Example 6

[0072] The difference between this embodiment and embodiment 1 is that, in addition to the Fe pretreated in step (2), 82 Si 9 Nb 6 B 2 Cu 1 Except that the mass ratio of nanocrystal to FeNi alloy powder is 1:0.4, the rest is the same as that of Example 1.

[0073] Example 7

[0074] The difference between this embodiment and embodiment 1 is that, in addition to the Fe pretreated in step (2), 82 Si 9 Nb 6 B 2 Cu 1 Except that the mass ratio of nanocrystal to FeNi alloy powder is 1:2.5, the rest is the same as that of Example 1.

[0075] Example 8

[0076] The only difference between this embodiment and embodiment 1 is that, except that the holding temperature for baking in step (3) is 130° C., the rest is the same as embodiment 1.

[0077] Example 9

[0078] The only difference between this embodiment and embodiment 1 is that, except that the holding temperature of baking in step (3) is 320° C., the rest is the same as embodiment 1.

[0079] Example 10

[0080] The only difference between this embodiment and embodiment 1 is that, except that the binder in step (3) is replaced by a combination of epoxy resin and dodecyltrimethylsilane, the rest is the same as embodiment 1.

[0081] Embodiment 11

[0082] The difference between this embodiment and embodiment 1 is that, in addition to the polyvinyl butyral ester and Al in step (3), 2 [(OH) 4 / Si 2 O 5 ], the mass ratio of epoxy resin and dodecyltrimethylsilane is 1:1:1:1, and the rest is the same as Example 1.

[0083] Example 12

[0084] The difference between this embodiment and embodiment 1 is that, in addition to the polyvinyl butyral ester and Al in step (3), 2 [(OH) 4 / Si 2 O 5 ], the mass ratio of epoxy resin and dodecyltrimethylsilane is 2:2:2:3, and the rest is the same as Example 1.

[0085] Comparative Example 1

[0086] The difference between this comparative example and Example 1 is that, in addition to the Fe pretreated in step (2), 82 Si 9 Nb 6 B 2 Cu 1 Except that the average particle size of the nanocrystals is 5 μm, the rest is the same as that of Example 1.

[0087] Comparative Example 2

[0088] The difference between this comparative example and Example 1 is that, in addition to the Fe pretreated in step (2), 82 Si 9 Nb 6 B 2 Cu1 Except that the average particle size of the nanocrystals is 55 μm, the rest is the same as that of Example 1.

[0089] Comparative Example 3

[0090] The only difference between this comparative example and Example 1 is that, except that the average particle size of the FeNi alloy powder in step (2) is 0.05 μm, the rest is the same as Example 1.

[0091] Comparative Example 4

[0092] The only difference between this comparative example and Example 1 is that, except that the average particle size of the FeNi alloy powder in step (2) is 11 μm, the rest is the same as Example 1.

[0093] Test Method

[0094] The magnetic composite materials obtained from Examples 1 to 12 and Comparative Examples 1 to 4 were subjected to a permeability test at 100kHz / 1V and a loss test at 1MHz / 50mT, respectively. The testing devices used were a WK6500B analyzer and a Japanese Iwasaki SY-8218BH analyzer, respectively. The test results are recorded in Table 1.

[0095] Table 1

[0096] Magnetic permeability (H / m) <![CDATA[Loss (mW / cm 3 )]]> Example 1 49 1726 Example 2 47 1764 Example 3 48 1758 Example 4 43 1864 Example 5 45 1793 Example 6 43 1796 Example 7 44 1836 Example 8 45 1824 Example 9 46 1795 Example 10 43 1788 Embodiment 11 45 1765 Example 12 44 1711 Comparative Example 1 35 2324 Comparative Example 2 32 2461 Comparative Example 3 30 2513 Comparative Example 4 36 2293

[0097] The test results show that:

[0098] (1) It can be seen from Examples 1 to 12 and Comparative Examples 1 to 4 that the present invention selects FeSiNbBCu nanocrystals and FeNi alloy powders of different particle sizes and reasonably matches the particle sizes between the two, so that the FeNi alloy powder with a small particle size can be fully filled into the particle pores of the FeSiNbBCu nanocrystals, thereby reducing the porosity of the magnetic composite material, improving its density, and also improving its magnetic properties. The method provided by the present invention has a simple process and is convenient for large-scale production. The prepared magnetic composite material can also reduce high-frequency losses while maintaining high magnetic permeability.

[0099] (2) It can be seen from Example 1 and Example 4-Example 5 that the magnetic composite material prepared by further regulating the holding temperature of the FeSiNbBCu nanocrystal annealing treatment in the present invention can further improve the magnetic permeability and reduce the loss.

[0100] (3) It can be seen from Examples 1 and 6-7 that the magnetic composite material prepared by further regulating the mass ratio of the pretreated FeSiNbBCu nanocrystals and the FeNi alloy powder can further improve the magnetic permeability and reduce the loss.

[0101] (4) It can be seen from Example 1 and Example 8-Example 9 that by further adjusting the baking insulation temperature, the magnetic composite material prepared by the present invention can further improve the magnetic permeability and reduce the loss.

[0102] (5) It can be seen from Example 1 and Example 10 to Example 12 that, by selecting a specific binder and further limiting the mass ratio of the binder components, the magnetic composite material prepared in the present invention can further improve the magnetic permeability and reduce the loss.

[0103] In summary, the present invention selects FeSiNbBCu nanocrystals and FeNi alloy powders of different particle sizes and reasonably matches the particle sizes between the two, so that the FeNi alloy powder with a small particle size can be fully filled into the particle pores of the FeSiNbBCu nanocrystals, thereby reducing the porosity of the magnetic composite material, improving its density, and also improving its magnetic properties. The method provided by the present invention has a simple process and is convenient for large-scale production, and the prepared magnetic composite material can also reduce high-frequency losses while maintaining high magnetic permeability.

[0104] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a magnetic composite material, characterized in that: The preparation method comprises the following steps: After mixing FeSiNbBCu nanocrystals, FeNi alloy powder and a binder, baking is performed to obtain the magnetic composite material; The average particle size of the FeSiNbBCu nanocrystals is 10 μm-50 μm; The average particle size of the FeNi alloy powder is 0.1 μm-10 μm.

2. The preparation method according to claim 1, characterized in that: The chemical formula of the FeSiNbBCu nanocrystal is Fe a Si b Nb c B d Cu e , where 5≤b≤20, 5≤c≤20, 0.5≤d≤15, 0.5≤e≤15, and a+b+c+d+e=100; Preferably, in the FeNi alloy powder, the mass ratio of iron to nickel is 1:(0.8-1.2).

3. The preparation method according to claim 1 or 2, characterized in that: The binder includes a combination of a first binder, a second binder, a third binder and a fourth binder; The first binder includes polyvinyl butyral; the second binder includes Al2[(OH)4 / Si2O5]; the third binder includes epoxy resin; the fourth binder includes dodecyltrimethylsilane; Preferably, the mass ratio of the first binder, the second binder, the third binder and the fourth binder is (1-2):(1-2):(2-3):(1-2).

4. The preparation method according to any one of claims 1 to 3, characterized in that The mass ratio of the FeSiNbBCu nanocrystals to the FeNi alloy powder is 1:(0.5-2); Preferably, the sum of the added mass amounts of the FeSiNbBCu nanocrystals and the FeNi alloy powder is M1, the added mass amount of the binder is M2, and M2 is 1%-2% of M1.

5. The preparation method according to any one of claims 1 to 4, characterized in that: Before the mixing, the FeSiNbBCu nanocrystals are also annealed; Preferably, the holding temperature of the annealing treatment is 550°C-650°C; Preferably, the holding time of the annealing treatment is 1h-5h.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The mixing method includes ball milling; Preferably, after the mixing and before the baking, compression molding is also performed; Preferably, the compression molding pressure is 300MPa-3000MPa.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The baking holding temperature is 150°C-300°C; Preferably, the baking insulation time is 1h-5h.

8. A magnetic composite material, characterized in that: The magnetic composite material is prepared by the preparation method according to any one of claims 1 to 7.

9. The magnetic composite material according to claim 8, characterized in that: The magnetic composite material has a magnetic permeability of ≥40H / m under the condition of 100kHz / 1V; Preferably, the loss of the magnetic composite material under the condition of 1MHz / 50mT is ≤2000mW / cm 3 .

10. Use of the magnetic composite material as claimed in claim 8 or 9, characterized in that: The magnetic composite material is applied to aerospace, communication or new energy.

Citation Information

Patent Citations

  • High-saturation flux density composite magnetic powder, magnetic core and preparation methods thereof

    CN107240471A

Cited By

  • Composite magnetic material, preparation method thereof and magnetic device

    CN121528672A